Performance of Turmeric and Soil Moisture Depletion Pattern Under Different Water Regimes and Nutrient Sources at New Alluvial Zone of Indo-Gangetic Plains, India. Issue 9 (15th May 2018) - Tripathi, Sandeep Kumar; Sharma, Babloo; Ray, R.; Raha, P.; Denis, Anjelo Francis
ABSTRACT: In India, the production of turmeric is not even half compared to its potential. To analyze the possibilities for higher production in turmeric, this study was conducted at the BCKV, Gayeshpur, West Bengal, during 2011 and 2012, to evaluate the effect of irrigation scheduling (0.6, 0.9, and 1.2 irrigation water (IW)/cumulative pan evaporation (CPE) and rainfed) in main plots and nutrient management [100% inorganic, 75% inorganic + 25% FYM (Farm yard manure), and 50% inorganic + 25% FYM + 25% vermicompost] in subplots on soil moisture depletion and productivity of turmeric. The highest value of fresh rhizome yield (23.90 kg ha −1 ) and qualitative indices were obtained with irrigation schedule at 0.9 IW/CPE ratio water regimes and 50% inorganic + 25% FYM + 25% vermicompost. The correlation coefficients of water use and yield of turmeric were found at 0.943. The combination of 0.9 IW/CPE and 50% inorganic + 25% FYM + 25% vermicompost improved the overall performance of turmeric crop.